PERSPEKTIF TENTANG ETIKA PROFESI MENURUT AKUNTAN PUBLIK DAN AKUNTAN PENDIDIK DI SURABAYA - HARYO WIDYASMONO, FRANSISKUS (: 2303-1719)
This study aims to determine the perception of public accountants and accounting educators on professional ethics. The analysis is based on respondents' answers obtained through a questionnaire distributed in Surabaya. The population of this research is a public accountant in Surabaya and accountants educators who work at 5 best accounting course in Surabaya that has accreditation namely A Widya Mandala Catholic University, Petra Christian University, Surabaya University, University Airlangga, STIE Perbanas. This study uses a sampling method. To examine differences in homogeneity of variance of data used Independent Sample T-Test Results of the study indicate there are differences in perceptions between public accountants and educators accountants on professional ethics. But not all the variables the study that states there are differences, there are two variables of the eight variables used in the study that states that there is no difference in perception between public accountants and educators accountants namely variable professional responsibility and integrity variables.